2015
DOI: 10.13189/aeb.2015.030301
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Farmer's Income with Production of Seaweed Eucheuma cottonii sp

Abstract: This paper examines the production of seaweedEucheuma cottonii sp as a major fishery commodity which produces carrageenan in supporting poverty eradication. The specific objectives are to determine factors of production in increasing seaweed production and to analyze income generated seaweed farmers in a harvest season. The research employed Multiple Linear Regression Analysis and Income Analysis. The results show that factors affecting the production of seaweed Eucheuma cottoni are long stretch (X 1 ), seed (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
1
2
0
2
Order By: Relevance
“…The result shows that the inexperience group (less than 10 years) has dominated the seaweed farming (Tabel 6.2). The finding is similar with the result shown by a previous study of Irmayani et al (2015), where they found that less experienced (3 to 10 years) group is also dominant in seaweed farming at Mallasoro Jeneponto, Indonesia. The present findings might be explained by some of the respondents who are fishermen, and they recently involve in seaweed farming as their secondary income generation.…”
Section: Resultssupporting
confidence: 91%
“…The result shows that the inexperience group (less than 10 years) has dominated the seaweed farming (Tabel 6.2). The finding is similar with the result shown by a previous study of Irmayani et al (2015), where they found that less experienced (3 to 10 years) group is also dominant in seaweed farming at Mallasoro Jeneponto, Indonesia. The present findings might be explained by some of the respondents who are fishermen, and they recently involve in seaweed farming as their secondary income generation.…”
Section: Resultssupporting
confidence: 91%
“…In the research, all respondents had productive ages, such as ranging from 36 -63 years. The average age of 45 years would affect the ability of farmers in terms of way of thinking, decision-making, and physical abilities [3,4,5] In addition, education was important for increasing productivity, such as formal education broadening farmers' minds to knowledge, non-formal education providing direct training to farmers and better methods, and informal education keeping farmers following innovations and changing ideas and allowing farmers to share experiences [6]. The results of the research show that formal education of most respondents was graduated from elementary school (62.5%), and the rest (37.5%) was junior high school.…”
Section: Respondents' Characteristicsmentioning
confidence: 99%
“…Serta kemampuan dalam langkah peningkatan budidaya rumput laut dengan cara mencari kualitas bibit yang baik, panjang bentangan, dan jarak ikat dapat mempengaruhi kualitas rumput laut. (Irmayani, S.Y., Arsyad, M., 2015).…”
Section: Ketercapaian Target Materi Dan Pelatihan Yang Telah Direncanunclassified